Household Latrine Utilization Behavioral Model as an Effort to Improve Open Defecation-Free Program - Hartatik, Erna; Rondhianto, Rondhianto; Helianti, Dina (Universitas Airlangga, 2024)
Background: Healthy latrine-using behavior indicates healthy behavior. However, many people still practice open defecation, which can cause illness and increase death risk. Self-efficacy is a dominant predictor of health behavior change. Aims: The study aims to develop a household latrine utilization behavior model based on self-efficacy to improve an open defecation-free (ODF) program. Method: The study was a descriptive-analytic with a cross-sectional design. The sample size was 138 respondents with cluster random sampling. The study variables were endogenous (household latrine utilization), exogenous (predisposing, enabling, and reinforcing factors), and intervening variables (self-efficacy). Data were collected by questionnaire and analyzed using SEM-PLS. Result: The household latrine utilization behavior-based self-efficacy model is fit (SRMR=0.098; NFI= 0.910; Q2=0.334). Valid and reliable indicators were education (predisposing), clean water availability and latrine maintenance (enabling), and health worker and family support (reinforcing). Path analysis showed exogenous factors, directly and indirectly, influence latrine utilization behavior through self-efficacy. Predisposing and reinforcing factors had a direct and significant effect (p = 0.025; p = 0.001) while enabling factors were insignificant (p = 0.438). Enabling and reinforcing factors indirectly and significantly affected latrine utilization behavior through self-efficacy (p = 0.033; p = 0.004), while predisposing factors were insignificant (p = 0.141). Self-efficacy significantly influenced latrine-using behavior (p = 0.023). Conclusion: The household latrine utilization behavior-based self-efficacy model is a fit model with good predictive relevance in predicting household latrine use behavior. Health workers can use the model to enhance household latrine utilization behavior and improve the ODF program and public health status.